In-Silico Approaches for Molecular Characterization, Structural Function Prediction and Peptide Toxicity Analysis of the Matrix Protein of Vesicular stomatitis Indiana Virus (VSIV) - S Ramya; R Shri Varshini; Sri R Poojaa; Prabhu Puniethaa (BIO Web of Conferences)
Vesicular Stomatitis Indiana Virus (VSIV) is a primary RNA virus studied for its effects in virology and in biotechnology the matrix protein of VSIV is key in linking the viral envelope to the core which is essential role in the assembly and release of viral particles. Through In silico approach the physicochemical properties secondary and tertiary structures and functional annotations of the matrix protein are analyzed, results indicate that the VSIV matrix protein is dominated by alpha-helical regions with a consistent tertiary structure validated by quality assessment methods. Peptide toxicity analysis of the matrix protein of VSIV focuses on evaluating the potential toxic effects of peptides derived from the matrix protein. Functional analysis confirms the protein role in forming virus particle. Molecular dynamic simulation to model the interaction of atoms and molecules and understand the behavior and properties of molecular structure in various condition.